Nuclide control of structural materials tested in electron irradiation test facility - Bakai, A.S.; Dovbnya, A.N.; Zykov, A.I.; Lavrinenko, S.D.; Myakushko, L.K.; Repikhov, O.A.; Torgovkin, A.V.; Shirokov, B.M.; Shramenko, B.I. (Вопросы атомной науки и техники, 2005)
Samples of different alloys (Hastelloy type) held in the container assembly (CA) were irradiated at the Electron Irradiation Test Facility (EITF) in the melt of zirconium and sodium fluorides at the temperature 650оС. The CA consisted of 16 individual containers made of a carbon-carbon (C-C) composite material (placed under covering shell made of stainless steel). The irradiation was done with electron beam at the energy in the spectrum maximum = 9.6 MeV at Linac-10 high-current accelerator that belongs to “Accelerator R&D Complex” affiliated with NSC KIPT. In order to secure the radiation-safe levels of the activity in further work with the samples, the focus of attention was paid to the analysis of γ-spectra in the remnant activities of the materials under study: Hastelloy type samples and fluoride salts after the irradiation. The dynamics was studied of decreasing of the activity levels of EITF components, sample assemblies in the containers being full with fluoride salts and individual samples. Recommendations are issued and measures taken to provide for further radiation-safe work with the irradiated materials.